Introduction - David Thomas Konig; Hon. David Mason; Karen L. Tokarz (Washington University Journal of Law and Policy, 2022)
In 2022, the Mound City Bar Association in St. Louis, one of the first Black bar associations in the country, celebrates its 100th anniversary. In this volume of the Washington University Journal of Law & Policy, distinguished authors look back at a century of contributions of Mound City Bar Association lawyers, judges, and allies, documenting their efforts to eliminate racial discrimination and break down barriers to equal justice. The volume is a testament to the work of countless individuals in the fight for civil rights since the beginning of the association in 1922. The authors also anticipate and examine the challenges ahead and the work yet to be done to achieve equal justice for all in our city, the region, and the country in the years to come.
Keywords: Mound City Bar Association in St. Louis; Centennial